Is ultrasound guided syringe-free method more efficient for saphenous vein catheterization? A prospective randomized controlled study - Öksüz, Gözen; Eroğlu, Erdinç (Journal of Surgery and Medicine, 2019)
Aim: Syringe-free is a novel technique without making blood aspiration with a syringe and by pushing forward the guide wire after verifying that the needle is inside the vein. In this study, we aimed to compare the vein intervention time between the ultrasound-guided syringe-free technique and the ultrasound-guided technique requiring syringe and aspiration procedures (classic technique), and also the success and complication rates of the first application. Methods: A prospective randomized controlled study was designed to compare ultrasound-guided syringe-free and ultrasound-guided classic technique in patients performed saphenous vein catheterization between June 2018 and September 2018. Demographic data, the period passed until a successful catheterization, the time for the needle to enter to the vein and the needle intervention number and complications are recorded. Results: 75 patient were enrolled in the study. There were no differences between demographical data in the patients (p>0.05). Vein puncture time were similar in each group (p=0.750). In the ultrasound-guided syringe-free group the catheterization time is determined to be significantly shorter (p=0.003). In the syringe-free method, it is determined that the successful catheterization number is higher at first try, but the difference is not determined to be significant (p=0.370). In both groups, central venous catheter-related complications were not observed during or after the procedure. Conclusion: In conclusion, an ultrasound-guided syringe-free approach can a decrease the duration of saphenous vein catheterization and allows the operator to perform the whole procedure with ultrasound guidance without interruptions. This method can be used as an advantageous and practical method for experienced operators.